Transcriptional Interference by Independently Regulated Genes Occurs in Any Relative Arrangement of the Genes and Is Influenced by Chromosomal Integration Position - Eszterhas, Susan K. (American Society for Microbiology, 2002)
Transcriptional interference is the influence, generally suppressive, of one active transcriptional unit on another unit linked in cis. Its wide occurrence in experimental systems suggests that it may also influence transcription in many loci, but little is known about its precise nature or underlying mechanisms. Here we report a study of the interaction of two nearly identical transcription units juxtaposed in various arrangements. Each reporter gene in the constructs has its own promoter and enhancer and a strong polyadenylation signal. We used recombinase-mediated cassette exchange (RMCE) to insert the constructs into previously tagged genomic sites in cultured cells. This strategy also allows the constructs to be assessed in both orientations with respect to flanking chromatin. In each of the possible arrangements (tandem, divergent, and convergent), the presence of two genes strongly suppresses expression of both genes compared to that of an identical single gene at the same integration site. The suppression is most severe with the convergent arrangement and least severe in total with the divergent arrangement, while the tandem arrangement is most strongly influenced by the integration site and the genes’ orientation within the site. These results suggest that transcriptional interference could underlie some position effects and contribute to the regulation of genes in complex loci.